2022
DOI: 10.3390/cancers14020317
|View full text |Cite
|
Sign up to set email alerts
|

The Overall Quality of Life and Oncological Outcomes Following Radical Hysterectomy in Cervical Cancer Survivors Results from a Large Long-Term Single-Institution Study

Abstract: (1) Background: Cervical cancer patients have been found to have worse quality of life (QoL) scores due to cancer treatment, not only when compared to the general population, but also when compared to other gynecological cancer survivors. In Eastern European developing countries, the health care system often cannot afford the uppermost standardized treatment for these patients. In the absence of a comparable study in our country, the authors’ aim for this retrospective cross-sectional observational study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a similar study, Stanca et al evaluated QoL 48 weeks after oncological treatment and obtained quite similar results related to symptom experience and functioning, except for lymphedema and peripheral neuropathy experiencing, which were found to be extremely high. However, it is necessary to mention that these results were calculated for patients treated with various methods and not exclusively with CCRT [33]. Another study of 90 participants demonstrated significantly worse functioning scores but significantly better symptom experience scores after chemoradiation compared with our study [26].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In a similar study, Stanca et al evaluated QoL 48 weeks after oncological treatment and obtained quite similar results related to symptom experience and functioning, except for lymphedema and peripheral neuropathy experiencing, which were found to be extremely high. However, it is necessary to mention that these results were calculated for patients treated with various methods and not exclusively with CCRT [33]. Another study of 90 participants demonstrated significantly worse functioning scores but significantly better symptom experience scores after chemoradiation compared with our study [26].…”
Section: Discussionmentioning
confidence: 48%
“…It was found that not a single participant reported good (sexual/vaginal functioning score ≥ 66.67) sexual/vaginal functioning, 57.1% (n = 4) indicated moderate (33.34-66.66), and 42.9% (n = 3) reported poor functioning (≤33. 33). An equally relevant question for assessing sexual function is the question about the experience of sexual enjoyment.…”
Section: Resultsmentioning
confidence: 99%
“…Lower-extremity lymphedema is the most common longterm effect following radical hysterectomy and has been associated with increased anxiety, depression and decreased selfconfidence, all contributing to a diminished quality of life [7,23]. The reported incidence of lymphedema secondary to cervical cancer surgeries varies widely, ranging from 7% to 55% [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Querleu-Morrow's classification categorizes radical hysterectomy into four types based on the extent of parametrial resection [6]. In addition, the degree of potential denervation following radical hysterectomy is directly linked to the extent of the surgery and its radicality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer with a ve-year survival rate of 60% 18 , many cervical cancer patients are young, socially and sexually active women whose QoL is at risk of being endangered by surgery treatment. A Romania research took translated standardized questionnaires, namely QLQ-C30 and QLQ-CX24 to assess their QoL after radical hysterectomy 19 . The questionnaires include functional scales, symptom scales, global health QoL scale and single items assessing symptoms 20 .…”
Section: Discussionmentioning
confidence: 99%